INTERPRETASI FRASA ADIL DAN LAYAK DALAM HUBUNGAN KERJA DALAM PASAL 28D AYAT (2) UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Panji Mulkillah Ahmad; Andy Omara (Mimbar Hukum, 2023)
Abstract Everyone wants treatment that “just and favourable in working relations”, as a right that is guaranteed by Article 28D paragraph (2) of the UUD 1945. However, the unclear meaning of this phrase raises problems of labor protection and uncertainty over the wage system. This article examines the meaning of the phrase “just and favourable in working relations” in the minutes of the Second Amendment to the UUD 1945 and the decisions of the Constitutional Court, as well as the implications of the unclear meaning of the phrase. This research is normative legal research with historical, casuistic, and conceptual approaches. The conclusions of this study: 1) The formulation of Article 28D paragraph (2) in the second amendment session of the 1945 Constitution originates from the MPR Decree Number XVII/MPR/1998 concerning Human Rights, which refers to the Universal Declaration of Human Rights and the International Covenant on Economic, Social and Cultural Rights. 2) The phrase “just and favourable in working relations” was interpreted differently by the Constitutional Court in several decisions. 3) There is no clear meaning in the decisions of the Constitutional Court for the phrase “just and favourable in working relations”. The Constitutional Court also did not interpret this phrase further with ILO recommendations and conventions which have clear criteria for a just and favourable work relationship. 4) This ambiguity has implications for workers not being protected in informal working relationships and changes in wage arrangements that do not refer to just and favourable work criteria. Abstrak Setiap orang mendambakan perlakuan “adil dan layak dalam hubungan kerja”, sebagai hak yang dijamin Pasal 28D ayat (2) UUD 1945. Namun ketidakjelasan makna atas frasa tersebut menimbulkan problem perlindungan tenaga kerja dan ketidakpastian sistem pengupahan. Artikel ini mengkaji makna atas frasa “adil dan layak dalam hubungan kerja” dalam risalah sidang Perubahan Kedua UUD 1945 dan putusan-putusan Mahkamah Konstitusi, serta implikasi ketidakjelasan makna atas frasa tersebut. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan historis, kasuistis dan konseptual. Kesimpulan penelitian ini: 1) Perumusan Pasal 28D ayat (2) dalam sidang perubahan kedua UUD 1945 bersumber dari Tap MPR Nomor XVII/MPR/1998 tentang Hak Asasi Manusia, yang merujuk ke Deklarasi Universal Hak Asasi Manusia dan Kovenan Internasional tentang Hak Ekonomi, Sosial dan Budaya. 2) Frasa “adil dan layak dalam hubungan kerja” diinterpretasikan MK secara berbeda dalam beberapa putusan. 3) Tidak terdapat makna yang jelas dalam putusan-putusan MK atas frasa “adil dan layak dalam hubungan kerja”. MK juga tidak menginterpretasi frasa tersebut lebih lanjut dengan rekomendasi dan konvensi ILO yang memiliki kriteria jelas hubungan kerja adil dan layak. 4) Ketidakjelasan tersebut berimplikasi pada tidak terlindunginya tenaga kerja dalam hubungan kerja informal dan perubahan-perubahan pengaturan pengupahan yang tidak mengacu pada kriteria kerja adil dan layak.